2020
DOI: 10.1089/heq.2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Adult Undocumented Immigrants in Accessing Primary Care: A Qualitative Study of Health Care Workers in Los Angeles County

Abstract: Purpose: Amid increasingly restrictive federal immigration and health care policies in the United States, access to health care for undocumented immigrants is highly dependent on the extent to which local and state policies and programs address the needs of this population. In Los Angeles County (LA County), home to the nation's largest undocumented immigrant population, supportive policies are in place, yet little is known about how undocumented immigrants navigate available services. Methods: To gain insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Our results are consistent with a prior study of African immigrants attending a health fair that found cost of care as a common barrier among a population with low levels of health insurance [10]. Barriers to insurance access include restrictive eligibility critiera, such as a five-year waiting period for Medicaid coverage, and the implementation of a redefined public charge rule is anticipated to have "chilling effects" on access to public assistance benefits, including health insurance [42][43][44][45][46]. Policies that impede immigrant use of welfare support or other public services have been linked to worse health outcomes [47,48].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are consistent with a prior study of African immigrants attending a health fair that found cost of care as a common barrier among a population with low levels of health insurance [10]. Barriers to insurance access include restrictive eligibility critiera, such as a five-year waiting period for Medicaid coverage, and the implementation of a redefined public charge rule is anticipated to have "chilling effects" on access to public assistance benefits, including health insurance [42][43][44][45][46]. Policies that impede immigrant use of welfare support or other public services have been linked to worse health outcomes [47,48].…”
Section: Discussionsupporting
confidence: 89%
“…Many of these barriers are structural in nature, such as lower rates of insurance coverage, cost, discrimination, language barriers, and lower health literacy among immigrants vs. non-immigrants, often compounded by inexperience among immigrants with the U.S. healthcare system [ 4 , 12 , 19 , 20 , 21 , 22 , 23 , 24 ]. Some immigrants also fear that using publicly-funded health care services or insurance might negatively impact immigration proceedings [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The theory of resource dependency emphasizes that the survival of an organization needs to absorb resources from the surrounding environment and needs to depend on and interact with the surrounding environment to achieve better survival [ 13 , 14 ]. Some studies have shown that place dependency is positively associated with the service quality of the place [ 15 ]. In other words, the better the service of a place, the more dependent the individual is on the place.…”
Section: Introductionmentioning
confidence: 99%